2016
DOI: 10.1037/gdn0000047
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association between relationship conflict and group performance.

Abstract: This laboratory study implemented the hidden profile paradigm in an attempt to assess whether group cohesion (both task and social) mediated the negative effects of relationship conflict on group performance. In the main, it was found that the negative effect of relationship conflict was mediated by task cohesion, but not by social cohesion. Instead, it was shown that social cohesion was better represented as a critical group-level outcome. That is to say, relationship conflict had indirect negative effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 43 publications
(96 reference statements)
3
29
0
1
Order By: Relevance
“…Of the aforementioned variables, group cohesion is of particular interest given its explanatory power. That is to say, group cohesion is often treated as a mediator of important group-level outcomes (Manata, 2016; Marks, Mathieu, & Zaccaro, 2001; Tekleab, Quigley, & Tesluk, 2009). Group cohesion is defined commonly as a critical group-level property that facilitates the general unification of the group and its members (Festinger, 1950; Lewin, Lippitt, & White, 1939).…”
Section: Lmx Lmx Differentiation and Group Cohesionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the aforementioned variables, group cohesion is of particular interest given its explanatory power. That is to say, group cohesion is often treated as a mediator of important group-level outcomes (Manata, 2016; Marks, Mathieu, & Zaccaro, 2001; Tekleab, Quigley, & Tesluk, 2009). Group cohesion is defined commonly as a critical group-level property that facilitates the general unification of the group and its members (Festinger, 1950; Lewin, Lippitt, & White, 1939).…”
Section: Lmx Lmx Differentiation and Group Cohesionmentioning
confidence: 99%
“…Group cohesion is defined commonly as a critical group-level property that facilitates the general unification of the group and its members (Festinger, 1950; Lewin, Lippitt, & White, 1939). Moreover, group cohesion can be further explicated by differentiating between its task and social aspects (Carron, Widmeyer, & Brawley, 1985; Dion, 2000; Manata, 2016; Tekleab et al, 2009). Specifically, task cohesion can be defined as a general attraction to and unison in completing the group’s task, whereas social cohesion can be defined as a general attraction to the group and its members (Castaño et al, 2013; Manata, 2016).…”
Section: Lmx Lmx Differentiation and Group Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…A main reason for why groups fail to achieve their aims is relationship conflict (Janss, Rispens, Segers, & Jehn, 2012;Manata, 2016). Three meta-analyses have demonstrated that relationship conflict between group members has a negative impact on group performance (DeDreu & Weingart, 2003;DeWit, Greer, & Jehn, 2012;O'Neill, Allen, & Hastings, 2013).…”
Section: Four Interpersonal Behaviors As Processes In the Prediction mentioning
confidence: 99%